1996
DOI: 10.1038/eye.1996.109
|View full text |Cite
|
Sign up to set email alerts
|

Peribulbar anaesthesia for cataract surgery: Prilocaine versus lignocaine and bupivacaine

Abstract: Prilocaine is a useful alternative anaesthetic agent for eye surgery that has low toxicity and is effective without adrenaline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…In a recent study comparing ropivacaine with bupivacainemepivacaine, a greater incidence of pain on injection was found in the bupivacaine-mepivacaine group (Luchetti et al 2000). Other studies have reported that only prilocaine was less painful than lidocaine or a lidocaine-bupivacaine mixture when injected (Henderson and Franks 1996;Bedi and Carabine 1999).…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study comparing ropivacaine with bupivacainemepivacaine, a greater incidence of pain on injection was found in the bupivacaine-mepivacaine group (Luchetti et al 2000). Other studies have reported that only prilocaine was less painful than lidocaine or a lidocaine-bupivacaine mixture when injected (Henderson and Franks 1996;Bedi and Carabine 1999).…”
Section: Discussionmentioning
confidence: 94%
“…A dense block usually develops at an acceptably rapid rate and is of adequate duration for all but the most prolonged surgery [10,11]. The principal drawback lies in the potential for cardiac and neurological toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[17]. Henderson and Franks, using the same VAS, reported scores of 1.03 for a 0.5% bupivacaine/1% lignocaine mixture with adrenaline and hyaluronidase and 0.88 for 2% prilocaine with hyaluronidase [11].…”
Section: ¹1mentioning
confidence: 99%
“…The peribulbar anaesthetic was administered at the junction of the middle and lateral thirds of the lower lid using a 1¼ (15/16″) 25 gauge needle (0.25×24 mm). Before surgery the patients were asked to grade the pain of both the preoperative dilating drops and the peribulbar injection on a standard visual analogue scale5 14 which was enlarged to A4 size to facilitate reading in these visually impaired patients—0 represents no pain and 10 the most severe pain imaginable. The questions were phrased identically in all patients.…”
Section: Methodsmentioning
confidence: 99%